1997
DOI: 10.1128/iai.65.6.2382-2388.1997
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory properties of porins of some members of the family Enterobacteriaceae

Abstract: The outer membrane protein (OMP) preparation of Salmonella typhi was observed to have several immunomodulatory properties. Treatment of mice with an intraperitoneal injection of the OMP preparation enhanced both cellular and humoral responses of the mice to an unrelated antigen, a killed vaccine of Mycobacterium vaccae; both the delayed-type hypersensitivity (DTH) response and the antibody titers were enhanced. The predominant isotype of the antibody shifted from immunoglobulin G1 (IgG1) to IgG2a upon treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The results obtained also indicate that the enterobacterial 38‐kDa OMP may be a candidate carrier for conjugate vaccines as a protein that is safe for use and that has the potential to produce protective antibodies. It was shown previously that porins, namely the 38‐kDa OMP of members of Enterobacteriaceae , have an adjuvant activity (Alurkar & Kamat, 1997; Ray et al , 2003), whereas the Th1 type of response, however, was favored with high antibody titers. Our results show that the reactivity of both IgA and IgG antibodies with OMP38 was significantly lower in children than in adult blood donors and increased gradually with age, although values for IgA were more distinct than those of IgG.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained also indicate that the enterobacterial 38‐kDa OMP may be a candidate carrier for conjugate vaccines as a protein that is safe for use and that has the potential to produce protective antibodies. It was shown previously that porins, namely the 38‐kDa OMP of members of Enterobacteriaceae , have an adjuvant activity (Alurkar & Kamat, 1997; Ray et al , 2003), whereas the Th1 type of response, however, was favored with high antibody titers. Our results show that the reactivity of both IgA and IgG antibodies with OMP38 was significantly lower in children than in adult blood donors and increased gradually with age, although values for IgA were more distinct than those of IgG.…”
Section: Discussionmentioning
confidence: 99%
“…Despite many efforts, there is a profound lack of immunomodulatory effect of the available surface antigens. The immunomodulatory effect of Shigella porin has been described to mediate antibody dependent B-cell responses (Alurkar and Kamat, 1997;Roy and Biswas, 1996). Small dose of S. flexneri OMPs has also been found to induce humoral as well as cell-mediated immune responses (Czarny et al, 1992;Sinha et al, 1992), whereas a higher dose suppresses Delayed Type Hypersensitivity (DTH) in mice (Chakrabarti and Sinha, 1994).…”
Section: Immunomodulatory Effect Of Surface Antigensmentioning
confidence: 99%
“…Immunomodulation of TLRs due to these bacterial outer membrane or secretory components have been studied in different in vitro conditions (Alurkar and Kamat, 1997;Wetzler et al, 1996) and has been shown to be involved in bacterial translocation leading to the activation of classical inflammatory responses through Nod-Like Receptors (NLR) innate signaling (Aliprantis et al, 2001;Phalipon and Sansonetti, 2007). Development of an effective immunomodulator using LPS as an adjuvant might trigger innate signaling via TLRs (Aliprantis et al, 2001;Alurkar and Kamat, 1997;Gribar et al, 2008). Recently, it has been reported that TLR activation is dependent on the number of acylated groups present in lipid A (Gribar et al, 2008;Rallabhandi et al, 2008).…”
Section: Patterns Recognition Receptors (Prrs)-specific Immunomodulatmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Similar to S. Typhi porins, it has been reported that other bacterial porins act as TLR agonists with adjuvant characteristics, including the Neisseria meningitidis PorB porin, 12 the Fusobacterium nucleatum FomA porin, 13 and Shigella dysenteriae porins. 14 Salmonella enterica serovar Typhi has been shown to express two genes encoding 373-amino-acid (41 000 molecular weight) 15 and 362-amino-acid (40 000 molecular weight) 16 OMPs, designated OmpS1 and OmpS2, respectively, and these porins contain motifs that are commonly found in other members of the porin superfamily. Expression of these proteins is strictly controlled by various regulators; under standard laboratory growth conditions, these porins are expressed at very low levels compared with the highly abundant OmpC and OmpF porins.…”
Section: Introductionmentioning
confidence: 99%